Griboedovistic Material in the Unknown Letters of A.P. Zavadovsky to P.A. Viazemsky - Sergey S. Minchik (Studia Litterarum)
Scholars who study the “duel of the four” which occurred in 1817, state that Alexander Griboedov, the author of Woe from Wit, was an involuntary witness of Vasily Sheremetev’s murder by Count Alexander Zavadovsky. However, until now the writer’s involvement in this event seems to have been overlooked. This could be due to the lack of contemporaneous sources related to the tragedy on the Volk’s Field. All relevant published materials have been used to investigate and reconstruct details of the incident, but none of them explains the impact that the death of Sheremetev had on the later life of its participants. The only exception are: Zavadovsky’s papers kept in P.A. Viazemsky’s personal fund in RSALA. Deciphered, processed, translated and introduced to the scholarly world, these materials will shed some light on what happened to Sheremetev’s murderer after the “duel of the four”: what his interests were, where he travelled, with whom he had relations with and how close he was to Griboedov. The transformation of Zavadovsky’s views is compared with those of the Russian author after the year of 1817; the conclusions of the essay correlate with Griboedov studies.